Odpowiedź:
wiadomości ogólne
funkcja kwadratowa w postaci kanonicznej
g(x) = a(x - p)² + q , gdzie p i q są współrzędnymi wierzchołka paraboli
a)
f(x) = 3x² + bx + c
a = 3 , W = (- 2 , 7 )
postać kanoniczna
f(x) = 3(x + 2)² + 7
Postać ogólna
f(x) = 3(x + 2)² + 7 = 3(x² + 4x + 4) + 7 = 3x² + 12x + 12 + 7 = 3x² + 12x + 19
b = 12 , c = 19
b)
f(x) = 2x² + bx + c
a = 2 , W = (- 1 , - 2 )
postać kanoniczna
f(x) = 2(x + 1)² - 2
postać ogólna
f(x) = 2(x + 1)² - 2 = 2(x² - 2x + 1) - 2 = 2x² - 4x + 2 - 2 = 2x² - 4x
b = - 4 , c = 0
c)
f(x) = √3x² + bx + c ,
a = √3 , W = (2 , 5 )
postać kanoniczna
f(x) = √3(x - 2)² + 5
postać ogólna
f(x) = √3(x - 2)² + 5 = √3(x² - 4x + 4) + 5 = √3x² - 4√3x + 4√3 + 5
b = - 4√3
c = 4√3 + 5